2016
DOI: 10.1080/02687038.2016.1147526
|View full text |Cite
|
Sign up to set email alerts
|

Implicit learning and implicit treatment outcomes in individuals with aphasia

Abstract: Background Implicit learning is a process of learning that occurs outside of conscious awareness and may be involved in implicit, exposure-based language training. However, research shows that implicit learning abilities are variable among individuals with aphasia, and it remains unknown whether individuals who show basic implicit learning abilities also benefit from implicit language training. Aims The aims of this series of experiments were to test implicit learning in individuals with agrammatic aphasia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…Clearly our study does not provide evidence that such a therapy would be more efficacious than existing methods for addressing asyntactic deficits after stroke, nor do we have any evidence of how well our strategies would work within an already-learned but now-impaired natural language. Indeed, a recent small study of nine patients who had chronic agrammatic aphasia secondary to stroke suggests that implicit learning alone (on a visuo-motor serial reaction time task) does not necessarily translate into improved real-world performance ( Schuchard et al, 2017 ). Larger scale trials and assessment with other tasks are clearly required in more acute disease cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly our study does not provide evidence that such a therapy would be more efficacious than existing methods for addressing asyntactic deficits after stroke, nor do we have any evidence of how well our strategies would work within an already-learned but now-impaired natural language. Indeed, a recent small study of nine patients who had chronic agrammatic aphasia secondary to stroke suggests that implicit learning alone (on a visuo-motor serial reaction time task) does not necessarily translate into improved real-world performance ( Schuchard et al, 2017 ). Larger scale trials and assessment with other tasks are clearly required in more acute disease cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with agrammatic aphasia show sequential learning in SRT tasks (Dominey et al, 2003; Goschke et al, 2001; Schuchard et al, 2017; Schuchard & Thompson, 2014), although they may be impaired in learning certain types of sequences (Goschke et al, 2001) or in learning the abstract underlying structures of sequences (Dominey et al, 2003). In contrast, Christiansen et al (2010) found no evidence of sequential learning in a group of seven agrammatic individuals who were exposed to an artificial grammar composed of visual shapes.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies examining sequential learning in people with agrammatic aphasia have shown mixed results. Several studies using serial reaction time (SRT) tasks, in which participants respond to a repeating sequence of stimuli, have shown evidence of sequential learning (Dominey et al, 2003; Goschke, Friederici, Kotz, & van Kampen, 2001; Schuchard, Nerantzini, & Thompson, 2017; Schuchard & Thompson, 2014). In contrast, artificial grammar learning studies, in which participants make judgments after exposure to multiple sequences of stimuli that follow an underlying rule structure, have shown abnormal learning ability in agrammatic aphasia (Christiansen et al, 2010; Zimmerer, Cowell, & Varley, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are the same anatomical regions that are activated during ISL tasks. This anatomical convergence has motivated a wealth of research that seeks to examine whether the syntactic impairment in Broca's aphasia might stem from a deficit in domain-general ISL mechanisms, rather than from a selective impairment to the syntax module (Cope et al, 2017;Dominey et al, 2003;Goschke et al, 2001;Schuchard and Thompson, 2013;Schuchard et al, 2016;Zimmerer et al, 2014). The majority of the aforementioned research has shown that patients with Broca's aphasia manifest impaired ISL abilities (but see Cope et al, 2017), which was suggested to support the hypothesis that ISL mechanisms play a prominent role in syntactic processing.…”
Section: Introductionmentioning
confidence: 99%